Formulasi Mouthwash Kulit Jeruk Pontianak (Citrus nobilis Lour. Var. microcarpa) dan Uji Aktivitas terhadap Bakteri Streptococcus mutans - Meri Ropiqa; Hadi Kurniawan; Sabila Mayesa (Sinteza, 2025)
Preserving dental and oral hygiene is essential to maintain the overall function of the oral cavity. Essential oil extracted from Pontianak orange peel shows potential as a safe and effective component for oral healthcare when incorporated into a mouthwash formulation. This research was conducted to evaluate the potential of Pontianak orange peel essential oil as an antibacterial mouthwash effective against Streptococcus mutans. The study was conducted by formulating mouthwash preparations using different concentrations of Pontianak orange peel essential oil: 3%, 4%, and 5%, followed by evaluation of physical properties including organoleptic characteristics, homogenity, pH level, sedimentation, specific gravity, and viscosity. The antibacterial properties were tested using  the disc diffusion method.The physical evaluation results showed that the mouthwash had a sweet taste, green color, a citrus peel aroma with a hint of mint; it was homogeneous, with no sedimentation; had a pH value ranging from 5.13 ± 0.02 to 5.25 ± 0.02; specific gravity ranging from 0.9968 ± 0.06 to 1.0424 ± 0.00 g/ml; and viscosity ranging from 1.717 ± 0.02 to 1.920 ± 0.01mPa.s. All formulations met the physical property requirements of a good mouthwash to ensure comfort during use. The largest inhibition zone was observed at the highest essential oil concentration (5%), with a diameter of 8.04 ± 1.05 mm, which falls under the category of moderate antibacterial activity. This study indicates that a mouthwash containing 5% Pontianak orange peel essential oil is effective in inhibiting the growth of Streptococcus mutans.